The Gender Politics of the Namibian Liberation Struggle - Akawa, Martha (Book collections on Project MUSE., 2014)
"Women's contributions against apartheid under the auspices of the Namibian liberation movement SWAPO and their personal experiences in exile take center stage in this study. Male and female leadership structures in exile are analysed whilst the sexual politics in the refugee camps and the public imagery of female representation in SWAPO's nationalism receive special attention. The party's public pronouncements of women empowerment and gender equality are compared to the actual implementations of gender politics during and after the liberation struggle"--Back cover